Modulation of lipidomic markers in oxidative stress neural-derived embryonic stem cell cultures with vitamin E supplementation - Abd Jalil, Afifah (2017)
Abnormal lipid metabolism is strongly related to the pathogenesis of Alzheimer’s disease (AD). Apolipoprotein E (APO E) is the major apolipoprotein in the CNS that has a role in cholesterol transport. Oxidative stress brain has reduced capacity for neuronal delivery of cholesterol suggesting a defect in cholesterol delivery for neuronal repair mechanism contribute to AD progression. Glutamate is the main excitatory neurotransmitter in the CNS, which can be excitotoxic at high concentration. Vitamin E has been shown to possess potent antioxidant and neuroprotection activities. It has two potent antioxidant isomers which are tocopherol and tocotrienol. In this present study, the effects of Tocotrienol Rich Fraction (TRF) from palm oil and alpha-Tocopherol (α-TCP) in modulating lipidomic markers in oxidative stress neural-derived embryonic stem (ES) cell cultures were elucidated. Transgenic mouse ES cell line (46C) was differentiated into neural lineage by induction with retinoic acid in vitro. The cells were then exposed to oxidative stress by a significantly high concentration of glutamate. Reactive oxygen species (ROS) measurement was done upon glutamate excitotoxicity and recovery processes by vitamin E were determined. Gene expression of glutamate receptors (NMDA and Kainate receptors), neuron-specific enolase (NSE), lipidomic markers including APO E, low density related protein (LRP) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) were elucidated using real-time PCR. The result reveals downregulation of NMDA, Kainate receptor, NSE and HMGCR upon posttreatment with different concentration of TRF and α-TCP in oxidative stress neural-derived 46C cells, a sign of neurorecovery process. Treatment of vitamin E also reduced the concentration of ROS to 33.05% and 57.2% upon 300ng/mL of TRF and α-TCP treatment respectively, in glutamate-induced oxidative stress neural cells which indicated that vitamin E is one of the potent antioxidants. In conclusion, TRF and α-TCP have protective and antioxidant properties against glutamate toxicity in neural derived ES cell and have the possibility to develop into potential treatment agents for AD.